Choosing the system configuration for high-volume manufacturing. Issue 1 (17th January 2018) - Koren, Yoram; Gu, Xi; Guo, Weihong
Abstract : When designing a new large manufacturing system with high throughput, the corporation should weigh several factors: the capital investment cost, the system's responsiveness to future varying market demand, the production losses due to disruptive events, and the product quality. These performance metrics depend heavily on the system configuration. In this paper, typical configurations of large-volume manufacturing systems for mechanical products are compared from cost, responsiveness and product quality perspectives. In addition to traditional serial lines and pure parallel systems, we also discuss two practical configurations – parallel serial lines, and reconfigurable manufacturing systems. The results offer managerial insights for selecting the system configuration that creates the maximum economic value over the lifetime of the system, and fits the corporation needs and culture.